2018
DOI: 10.1021/acs.langmuir.8b02657
|View full text |Cite
|
Sign up to set email alerts
|

Bile Salts: Natural Surfactants and Precursors of a Broad Family of Complex Amphiphiles

Abstract: Bile salts (BSs) are naturally occurring rigid surfactants with a steroidal skeleton and specific self-assembly and interface behaviors. Using bile salts as precursors, derivatives can be synthesized to obtain molecules with specific functionalities and amphiphilic structure. Modifications on single molecules are normally performed by substituting the least-hindered hydroxyl group on carbon C-3 of the steroidal A ring or at the end of the lateral chain. This leads to monosteroidal rigid building blocks that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 134 publications
1
53
0
Order By: Relevance
“…We found that the SIF does not show a CMC, as the surface tension does not display a steep decrease at a given concentration value (data not shown). Again, this is in agreement with the literature, as many data suggest that for bile salts the transition from monomeric to micellar solution occurs stepwise over a broad range of concentrations [20,27].…”
Section: Sif Characterizationsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the SIF does not show a CMC, as the surface tension does not display a steep decrease at a given concentration value (data not shown). Again, this is in agreement with the literature, as many data suggest that for bile salts the transition from monomeric to micellar solution occurs stepwise over a broad range of concentrations [20,27].…”
Section: Sif Characterizationsupporting
confidence: 92%
“…These media typically consist of aqueous solutions of bile salts (anionic natural steroidal surfactants, typically sodium taurocholate) and phospholipids (such as lecithin, a mixture of phosphatidylcholines), in addition to other components that allow the fluid to mimic the pH, the osmolality and the buffer capacity of each specific tract of the gut [18,19]. The simultaneous presence in solution of bile salts and lecithin often results in the formation of self-assembled structures, such as mixed micelles, depending on their molar ratio, concentration, pH, ionic strength and temperature [19,20]. In the mixed micelles, which are also present in vivo and allow for the solubilization and absorption of dietary fats [21], bile salts are located between polar head groups of phospholipids, with their hydrophilic sides exposed to the aqueous environment; this results in the formation of either spherical, cylindrical or worm-like micelles, with sizes ranging from 3.5 to 70 nm, depending on the phospholipid and bile salt amount and their ratio [19,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…32 BSs, like NaDC, have a steroidal molecular structure, which is completely different from the typical head-tail one of conventional surfactants. 33,34 This governs their self-assembly in solution forming structures with specific supramolecular arrangements, e.g., globular, rod-like or tubular morphologies. 33,35 as well as hexagonal liquid crystalline phases.…”
Section: Introductionmentioning
confidence: 99%
“…The SPA using bile acid salts as building blocks has been well‐developed due to their unique rigid amphiphilic structure . These bile acid salts might bind with various metal ions to form SPA, which could behave as hydrogels through synergistic effect .…”
mentioning
confidence: 99%
“…DOI: 10.1002/marc.201900182 structure. [9] These bile acid salts might bind with various metal ions to form SPA, which could behave as hydrogels through synergistic effect. [10] The metal-cholate electrostatic interaction and the hydrogenbonds between the cholate work in concert to construct various supramolecular nanostructure.…”
mentioning
confidence: 99%